Negative response to immunotherapy in dMMR or MSI-H gastric cancer with APC and PTEN mutations: a case report - Jiang Liu; Xiumei Zhang; Qun Ren; Chuanjun Song; Jianhe Yu; Yin Cai; Dadong Chen (Frontiers in Oncology)
BackgroundMicrosatellite instability-high (MSI-H) or deficient mismatch repair (dMMR) represents a distinct molecular phenotype observed in malignant tumors. These tumors typically exhibit high levels of programmed cell death 1 ligand 1 (PD-L1) expression and high tumor mutational burden (TMB), resulting in an enhanced response to immune checkpoint inhibitors (ICI) therapy. The emergence of ICI has transformed the therapeutic strategy of gastric cancer (GC). Immune checkpoint blockade significantly improves the survival of gastric cancer patients, especially those with MSI-H or dMMR. However, it’s worth noting that not all patients with MSI-H respond favorably to this treatment. It has been reported that factors such as tumor heterogeneity, alterations in the tumor microenvironment, and aberrant activation of tumor-related signaling pathways have been linked with resistance to ICI therapy.Case presentationHere, we describe a case of dMMR and MSI-H GC with adenomatous polyposis coli (APC) and phosphatase and tensin homolog deleted on chromosome ten (PTEN) mutations that failed to respond to anti-PD-1 combined with anti-HER2 (human epidermal growth factor receptor-2) therapy and chemotherapy. We attempted to elucidate the underlying causes and mechanisms behind this lack of response, and to provide new insights into treatment options for these patients.ConclusionsMutations of key genes within tumor-related signaling pathways and the infiltration of CD8+T cells in the tumor microenvironment may influence the efficacy of immunotherapy for MSI-H solid tumors.